Factors influencing the intention of the intensive care unit nurses to take preventive measures against deep vein thrombosis: a multicenter, cross sectional study - Nie, Jing; Jiang, Zhengying (Frontiers in Medicine, 2025)
PurposeTo assess the current situation and factors influencing the ICU nurses’ intention to take measures to prevent deep vein thrombosis, and to provide a reference basis for developing strategies to intervene in the same.MethodsA questionnaire survey was conducted on 575 ICU nurses in 16 tertiary care hospitals across China, including a general information questionnaire and the Chinese Version of Nurses’ Intention to Use Deep Vein Thrombosis Preventive Measures Questionnaire (C-NUDQ), to assess the current situation of the ICU nurses’ intention to take preventive measures against deep vein thrombosis (DVT) and to analyse the influencing factors.ResultsThe total score of the ICU nurses’ intention to take measures to prevent DVT was (93.32 ± 12.62), of which the intention dimension score was (19.24 ± 2.84), behavioural attitude dimension score was (26.34 ± 3.37), subjective normative dimension score was (25.28 ± 3.89), and perceived behavioural control dimension score was (22.46 ± 4.70). The results of multiple linear regression analysis showed that education, years of ICU work, ICU specialist nurses, and they with training in knowledge related to DVT were the main influencing factors in the ICU nurses’ intention to take measures to prevent DVT.ConclusionThe intensive care unit nurses’ overall intention to adopt deep vein thrombosis preventive measures was at a moderately high level, and the remaining dimension scores that ranked from the highest to the lowest were for behavioural attitude, subjective norm, and perceived behavioural control. Education, years of intensive care unit work, they are intensive care unit specialist nurses, and they had received training in deep vein thrombosis-related knowledge were the influencing factors for the intensive care unit nurses’ intention to take preventive measures against deep vein thrombosis.